2021
DOI: 10.1097/ju.0000000000001784
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Rates of Gynecologic Organ Involvement in Females with Muscle Invasive Bladder Cancer: A Retrospective Review of Women Undergoing Radical Cystectomy following Neoadjuvant Chemotherapy

Abstract: Conclusions: Even among high risk patients with MIBC, gynecologic organ involvement of MIBC is rare, and organ preservation, especially of the ovaries, is likely safe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…According to a systematic review, up to one-fourth of the women are affected by metastatic recurrence after an organpreserving approach, similar to ORC and LRC (29). On the other hand, a recent retrospective study did not find any differences in survival outcomes for ROPRC compared to non-ROPRC in women with variant histology and it was suggested, also by other studies, that presence of advanced disease does not preclude ROPRC (33,34).…”
Section: Oncological Safety Of Roprcmentioning
confidence: 95%
“…According to a systematic review, up to one-fourth of the women are affected by metastatic recurrence after an organpreserving approach, similar to ORC and LRC (29). On the other hand, a recent retrospective study did not find any differences in survival outcomes for ROPRC compared to non-ROPRC in women with variant histology and it was suggested, also by other studies, that presence of advanced disease does not preclude ROPRC (33,34).…”
Section: Oncological Safety Of Roprcmentioning
confidence: 95%
“…Ovarian cancer is rare among women undergoing RC. In a retrospective study by Bree et al of 149 women undergoing RC in the era of neoadjuvant chemotherapy, no patient had primary ovarian malignancy or urothelial cancer involving the ovary [16 ▪▪ ]. Among women who did not undergo BSO at the time of RC, there were no episodes of urothelial recurrence in the ovaries and/or development of primary ovarian malignancy during a median of 32.1 months of follow-up [16 ▪▪ ].…”
Section: Ovarian Preservation and Sexual Functionmentioning
confidence: 99%
“…In a retrospective study by Bree et al of 149 women undergoing RC in the era of neoadjuvant chemotherapy, no patient had primary ovarian malignancy or urothelial cancer involving the ovary [16 ▪▪ ]. Among women who did not undergo BSO at the time of RC, there were no episodes of urothelial recurrence in the ovaries and/or development of primary ovarian malignancy during a median of 32.1 months of follow-up [16 ▪▪ ]. Similarly, in a SEER analysis, Abboud et al [17] found just two cases of subsequent ovarian cancer among 1851 women who underwent RC for BC between 1998 and 2010.…”
Section: Ovarian Preservation and Sexual Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgery and traditional chemotherapy are still the current standard treatment for BC patients [ 2 ]. However, the high mortality rate caused by tumor recurrence and metastasis after treatment is a major clinical problem that urgently needs to be resolved [ 3 ]. Therefore, exploring new treatments for BC has been a huge clinic demand.…”
Section: Introductionmentioning
confidence: 99%